Penerapan Metode WASPAS pada Sistem Pendukung Keputusan Pemilihan Perusahaan Sekuritas - Aldyansyah, Kevin; Pramudhita, Agung Nugroho; Subhi, Dian Hanifudin (UNIVERSITAS SERAMBI MEKKAH, 2024)
The selection of a credible securities company is the first step for investors to start investing in stocks. A securities company is a stock trading intermediary between investors and the company whose shares will be purchased. Credible securities companies must be listed on the Indonesia Stock Exchange (IDX) and followed by the Financial Services Authority (OJK). The limited information possessed by potential investors regarding the quality of securities companies causes them to hesitate in buying shares. Therefore, a decision support system is needed in the selection of this securities company. This study aims to facilitate potential investors in determining securities companies in conducting share purchase transactions using the Weighted Aggregated Sum Product Assessment (WASPAS) method. The criteria used in the intercompany valuation of securities are: initial deposit fee, transaction fee, number of registered users, adjusted net working capital, and available features or services. This method is a weighted sum of the performance assessments on each alternative to all attributes. In this study, thirteen securities were used as alternatives in Malang, namely Mirae Asset, Indo Premier, BRI Sekuritas, BNI Danareksa, Mandiri, RHB, Trigemah, MNC, Valbury, Sinarmas, Reliance, Uob Kay Hian, and Sucor Sekuritas. Based on this research, system calculations using the WASPAS method provide the same results as the manual calculations performed on Microsoft Excel. The implementation of the ranking process on the accuracy answers is quite good, with an accuracy level of 73.3% from 5 respondents who have tested. This system can be used as an option for the selection of securities companies in the city of Malang with a fairly good accuracy rate of 73.3%.